KARAKTERISTIK HABITAT TEMPAT BERTELUR PENYU DI KAWASAN TAMAN WISATA ALAM TANJUNG BELIMBING KECAMATAN PALOH KABUPATEN SAMBAS - Manurung, Berman; Erianto, .; Rifanjani, Slamet (Universitas Tanjungpura, 2016)
Sea turtles are a protected animal because its population is almost extinct. There are six species of sea turtles in Indonesia, the only one species of turtle that was never found in Indonesia is camps's ridley sea turtle (Lepidochelys kempi). Six species of sea turtles are found in Indonesia’s water are leatherbacks (Dermochelys cociacea), green turtle (Chelonia mydas), hawksbill (Eretmochelys imbricata) and Olive Ridley turtles (Lepidochelys olivacea), turtle flat (Natator depressus), loggerhead (Caretta caretta). Four endangered species of sea turtles are leatherback turtle (Dermochelys cociacea), green turtle (Chelonia mydas), hawksbill (Eretmochelys imbricata) and Olive Ridley turtles (Lepidochelys olivacea). The research was conducted in ​​the Nature Park District area of Tanjung Belimbing Paloh, Sambas using observationmethod. These observations were made on the area that has 9193 meters long coastline and beach slope 6-12%. Result of field analysis showing that was the turtle nesting habitat characteristics was sand temperature 28.2 ° C - 29.8 ° C, sand moisture content 5.2%, 99.43% texture of sand, temperature air 23 ° C - 29 ° C, humidity 73% - 79%. During the study has been found four green turtles (Chelonia mydas) with the longest carapace was 120 cm, the shortest carapace was 90 cm, the biggest carapace width was 85 cm and the smallest was 66 cm. The turtle nesting time ranging between 20:00 pm - 2:00 pm. The threat like beach abrasion. The biggest threat still comes from human action and behavior where turtle’s egg used for consumption, trade and habitat destruction due to the garbage that comes from the sea. Keywords: Habitat characteristics sea turtles, TWA Tanjung Belimbing